Optimization of Jiuzao protein hydrolysis conditions and antioxidant activity in vivo of Jiuzao tetrapeptide Asp-Arg-Glu-Leu by elevating the Nrf2/Keap1-p38/PI3K-MafK signaling pathway. Issue 11 (20th April 2021) - Jiang, Yunsong; Wang, Rui; Yin, Zhongtian; Sun, Jinyuan; Wang, Bowen; Zhao, Dongrui; Zeng, Xin-an; Li, Hehe; Huang, Mingquan; Sun, Baoguo
Abstract : Tetrapeptide DREL from Jiuzao exhibits antioxidant and anti-inflammatory activities through activating the Nfr2/Keap1-p38/PI3K-MafK signaling pathway and downstream antioxidant enzymes. Abstract : Tetrapeptide Asp-Arg-Glu-Leu (DREL) was isolated from Jiuzao protein hydrolysates (JPHs) by alkaline proteinase ( AP ) and exhibited antioxidant activity in the HepG2 cell model in the previous study. In this study, the hydrolysis method of Jiuzao protein (JP) was further optimized by using different proteinases under different conditions ( i.e., temperature, time, ratio between proteinase and substrate, and pH). Considering the limitation of in vitro assays, the AAPH-induced oxidative stress Sprague-Dawley (SD) rat model was selected to measure the antioxidant capacity of DREL in vivo . Pepsin exhibited the highest hydrolysis degree under the optimum conditions after single factor analysis (SFA) among seven proteinases. The total yield of DREL in Jiuzao was 158.24 mg kg −1 Jiuzao under the pepsin's optimum hydrolysis conditions determined by response surface methodology analysis (RSMA). In addition, DREL could activate the Nrf2/Keap1-p38/PI3K-MafK signaling pathway and downstream antioxidant enzymes to improve the antioxidant ability in vivo . DREL also preliminarily exhibited anti-inflammatory activity by inhibiting the secretion of inflammatory cytokines and the mediator through the activation of Nrf2. Of note, the addition of DREL in baijiu brought an inconspicuous change in the taste after sensory evaluation. This study finds out the better proteinase used for JP hydrolysis and verifies the antioxidant capacity of DREL in vivo, which provides a potential approach to apply functional components from Jiuzao for by-product utilization. Meanwhile the antioxidant function of baijiu or other foods can be increased through adding these functional peptides without affecting the original flavor and taste in the future.